2008
DOI: 10.1038/ismej.2008.94
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of Bacteria and Archaea and amoA gene copy numbers throughout the water column of the Eastern Mediterranean Sea

Abstract: Until recently, ammonia oxidation, a key process in the global nitrogen cycle, was thought to be mediated exclusively by a few bacterial groups. It has been shown now, that also Crenarchaeota are capable to perform this initial nitrification step. The abundance of ammonia oxidizing Bacteria and Archaea was determined using the bacterial and archaeal ammonia monooxygenase-a subunit (amoA) gene as functional markers in a quantitative PCR approach and related to the abundance of Bacteria and Archaea in the Easter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
77
5
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 32 publications
11
77
5
1
Order By: Relevance
“…The number of archaeal OTUs obtained in this study was lower than in previous studies on the deep tropical East Atlantic (Winter et al, 2008) and in the deep Eastern Mediterranean Sea (Moeseneder et al, 2001a b;De Corte et al, 2009).…”
Section: Viral and Heterotrophic Prokaryotic Productioncontrasting
confidence: 50%
“…The number of archaeal OTUs obtained in this study was lower than in previous studies on the deep tropical East Atlantic (Winter et al, 2008) and in the deep Eastern Mediterranean Sea (Moeseneder et al, 2001a b;De Corte et al, 2009).…”
Section: Viral and Heterotrophic Prokaryotic Productioncontrasting
confidence: 50%
“…Also, the ratio of MG1C amoA genes to MG1C 16S rRNA genes in these samples was 0.51 ( Figure 1b). Although lower than values reported for ammonia-oxidizing enrichments (Wuchter et al, 2006) or cultures (Konneke et al, 2005) (1:1 to 2.8:1) or the gene dosage in MG1C genomes (1:1) (Hallam et al, 2006a;Walker et al, 2010), this ratio is much higher than ratios used to infer heterotrophy in other populations de Corte et al, 2008;Kalanetra et al, 2009).…”
Section: Ammonia Uptake and Oxidationmentioning
confidence: 53%
“…Studies of the distributions of planktonic ammonia oxidizing organisms have shown that ammonia-oxidizing Crenarchaeota (ammoniaoxidizing archaea, AOA) tend to be numerically dominant in the open ocean (Wuchter et al, 2006;Mincer et al, 2007;Agogue et al, 2008;Beman et al, 2008;de Corte et al, 2008;Kalanetra et al, 2009;Santoro et al, 2010) and fjords Zaikova et al, 2010). Most studies of AOA populations in estuaries (Francis et al, 2005;Beman and Francis, 2006;Caffrey et al, 2007;Mosier and Francis, 2008;Santoro et al, 2008;Magalhaes et al, 2009;Bernhard et al, 2010) have focused on sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, abundances of the 16S rRNA and the amoA genes differ markedly. Studies in marine environments reported an archaeal amoA to 16 S ratio of 0.5:1 and lower (De Corte et al, 2009). In Lake Redon ratios of 5:1-8:1 were observed, suggesting that either not all 16S genes of amoA gene containing organisms were detected with the qPCR assay or that the archaea present in the lake have a higher copy number of amoA genes per genome.…”
Section: Discussionmentioning
confidence: 99%